An audit on the use of chaperones during intimate patient examinations. (May 2016) - Sharma, Nikhil; Kathleen Mary Walsh, Aideen; Rajagopalan, Sriram
Abstract: Background: The general medical council stipulate all intimate examinations should be chaperoned, and their identity documented within patients' notes. We decided to audit our surgical unit for compliance to these guidelines. Methods: A prospective audit before and after intervention was performed. Patients undergoing an intimate examination on the surgical assessment unit over five working days were recruited. Data was collected for the following: chaperone use, identity or decline by a patient. Statistical significance calculated using the unpaired t -test. Intervention following audit results included design of a chaperone sticker and posters to act as an aide memoir to clinicians. Results: 61 patients recruited before intervention. Examination of notes revealed documentation of chaperone use in 10patients(16.4%), identity in 9patients(14.8%) and decline in 3patients(4.9%). Chaperone documentation was found in only 13 medical notes(21.3%). After two-months of intervention, 53patients were recruited. Analysis revealed documentation of chaperone use in 27patients(50.9%), identity in 20patients(37.7%) and decline in 5patients(9.4%). Following intervention chaperone documentation was found in 32 medical notes, an improvement to 60.3%(p = 0.0001). Conclusion: A chaperone should be offered to all patients who undergo an intimate examination. The identity of the chaperone or decline by a patient should be documented within their medical notes. Our team have demonstrated how effective an audit tool is to improve compliance to guidelines, patient safety and care. A further audit will be undertaken once our surgical proformas have been redesigned to incorporate an area for the chaperone to sign and we encourage other surgical units to do the same. Highlights: Intimate patient examinations should be chaperoned and their identity documented. Providing medial legal protection to clinicians and ensuring patient safety. Using a chaperone sticker we have increased compliance to chaperone documentation. And urge other surgical units to do the same, protecting both clinician and patient.